THE EFFECTIVENESS OF BANK SYARIAH INDONESIA INTEGRATION IN IMPROVING THE NATIONAL ECONOMY - Aisyah Rahmawati, Fithria (UIN Salatiga, 2021)
PT Bank Syariah Indonesia, Tbk (BSI) as a sharia financial institution as a result of the merger of 3 sharia banks (Bank Syariah Mandiri, BRI Syariah and BNI Syariah) has officially been operating. BSI exists as an effort to encourage larger Islamic banks so that they can enter the global market and become a catalyst for sharia economic growth in Indonesia. After the merger, BSI has carried out the integration process in various sectors. In this qualitative research with this type of evaluation, the researcher will examine the integration process of the Indonesian Islamic Bank to see how effective it is in improving the national economy. Currently, the entire network of Bank Syariah Indonesia has been integrated with a single system or one system. This service system integration is one of the operational merger steps and can support BSI services to run more optimally. Through innovation in the integration process, BSI services run more effectively and efficiently where customers can transact more conveniently, easily and safely. BSI has very strong assets and liquidity through the merger of three large Islamic banks so that it will be more flexible to expand its business and expand the reach of Islamic financial services starting from the MSME segment, retail, to large-scale corporations. BSI is expected to be an accelerator for the development of the sharia economy in Indonesia. BSI is also believed to have a positive impact on the development of the sharia economy, because the new entity born from this corporate action will have large capital to move into driving national economic growth.